A Prevalence and Predictors of Diabetic Retinopathy among Newly Diagnosed Type 2 Diabetes Mellitus Patients in Benghazi, Libya: A Cross-Sectional Study - Ibrahim, Najah; Sanfaz, Muataz (AlQalam Journal of Medical and Applied Sciences, 2025)
Diabetic Retinopathy [DR] is a leading cause of visual impairment among adults with diabetes. Early detection is crucial, as retinal changes may be present at the time of Type 2 diabetes mellitus [T2DM] diagnosis. Limited data exist regarding the early occurrence of DR in the Libyan population. This study was conducted to assess the prevalence of DR and identify associated risk factors among newly diagnosed T2DM patients. A cross-sectional observational study among 89 newly diagnosed T2DM patients attending the Ophthalmology Outpatient Department at Benghazi Eye and Ophthalmic Surgery Teaching Hospital. Comprehensive ophthalmological examinations were performed, including dilated fundus assessment. Sociodemographic and clinical variables such as age, gender, duration since diagnosis, smoking status, hypertension, hyperlipidemia, BMI, and HbA1c were recorded. The mean age of participants was 52.66 ± 7.4 years, with a female predominance [60.7%]. The prevalence of DR was 13.5% [12/89]. No significant association was observed between DR and gender, age, smoking status, BMI, hypertension, or hyperlipidemia [p > 0.05]. Logistic regression indicated a borderline association between elevated HbA1c levels and DR [AOR = 1.25, 95% CI: 0.98–1.59, p = 0.068]. DR is present in a notable proportion of patients at T2DM diagnosis, highlighting the likelihood of delayed disease recognition. Early retinal screening and strict glycemic control are essential strategies to prevent progression of sight-threatening complications. Further multicenter studies with larger sample sizes are recommended for broader generalization.